2018
DOI: 10.1007/s10557-018-6785-y
|View full text |Cite
|
Sign up to set email alerts
|

Old Drugs for New Indications in Cardiovascular Medicine

Abstract: Inflammation participates in the initiation and progression of atherosclerotic cardiovascular disease, and it is a critical inciting factor leading to acute ischemic events. Evidence has shown that certain anti-inflammatory medications used to treat non-atherosclerotic inflammatory diseases reduce cardiovascular events. This article reviews evidence that commonly used anti-inflammatory therapies (colchicine, allopurinol, methotrexate), reduce cardiovascular events. We discuss potential mechanisms of action, ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Besides its cholesterol-lowering properties, atorvastatin also possesses pleiotropic anti-inflammatory effects that could help the management of RA activity. [7][8][9][10][11][12][13][14][15][17][18][19][20]22 The pooled results of the present systematic review and meta-analysis of 8 RCTs support that atorvastatin could be added to DMARDs in patients with RA for disease control, but it has to be noted that the heterogeneity of the available data was high.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Besides its cholesterol-lowering properties, atorvastatin also possesses pleiotropic anti-inflammatory effects that could help the management of RA activity. [7][8][9][10][11][12][13][14][15][17][18][19][20]22 The pooled results of the present systematic review and meta-analysis of 8 RCTs support that atorvastatin could be added to DMARDs in patients with RA for disease control, but it has to be noted that the heterogeneity of the available data was high.…”
Section: Discussionmentioning
confidence: 73%
“…In recent years, numerous studies have demonstrated that statins can contribute to the anti-inflammatory management of RA symptoms 7–22 . Statins are a class of lipid-lowering agents and prevent the production of cholesterol in the liver by inhibiting the 3-hydroxy-3-methyl-glutaryl coenzyme A (HMG-CoA) reductase 23,24 .…”
mentioning
confidence: 99%
“…To date, the only therapeutic solutions for cardiac dysfunctions are drugs and/or heart transplantation. [37][38][39] Based on that, new treatments are needed for treating cardiovascular diseases, that represents the worldwide leading cause of deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Results from LoDoCo-MI (a pilot randomized placebo-controlled trial of colchicine after acute MI) shows that treatment with 0.5 mg/day of colchicine was not associated with a significantly increased likelihood of achieving a CRP level < 2 mg/L or lower absolute levels of CRP 30 days after an acute MI (75). In terms of the mechanism, colchicine is a dose-dependent, broad-spectrum anti-inflammatory drug (64), and colchicine inhibits inflammation via NOD-like receptor family pyrin domain containing 3 (NLRP3) (NOD-, leucine-rich repeats-, and pyrin domain-containing protein 3); inflammasome is believed to act as a key mechanism in coronary arteriosclerotic heart disease (76)(77)(78)(79). NLRP3 is an intracellular sensor, and the activation of NLRP3 inflammasome leads to caspase 1-dependent release of the pro-inflammatory cytokines IL-1β (80).…”
Section: Anti-inflammatory Effects Of Colchicine In Atherosclerotic Heart Disease Need Further Evaluationmentioning
confidence: 99%